Born Entrepreneurs? Immigrant Self-Employment in Spain - Irastorza, Nahikari (IMISCoe Dissertations, 2010)
Are immigrants more enterprising than natives in Spain? How successful are migrant entrepreneurs compared to those who start businesses in their country of birth? With the growth of migration worldwide, questions such as these are garnering the attention of economists, policymakers and scholars. Born Entrepreneurs? asks how foreignness affects an immigrant's ability to launch and to grow a successful business. It also explores the economic and social benefits that immigrants might derive from self-employment and the unique factors at play in so-called ethnic and immigrant entrepreneurship.